2014
DOI: 10.1155/2014/390158
|View full text |Cite
|
Sign up to set email alerts
|

Do Building Information Modelling Applications Benefit Design Teams in Achieving BREEAM Accreditation?

Abstract: Using building information modelling (BIM) within a design team allows for integration of sustainability analysis such as daylighting analysis, water harvesting, and thermal assessment whilst capturing the data which can be used for BREEAM assessment. Therefore, the availability of data compared to traditional methods can be used to design teams, stakeholders, and environmental assessment bodies’ advantage. Since BIM boasts extensive building performance analysis capabilities, design teams should be provided w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 9 publications
0
4
0
1
Order By: Relevance
“…Moreover, some skilled and experienced teams including design teams can better the operation of the company, so the top management is willing to spend money to support the BIM development in the company further. Interviewee C considered item 5 – client’s acceptance with BIM projects (Harding et al , 2014; Kassem et al , 2012) as also vital. For item 5, different clients have their concerns and needs.…”
Section: Discussion Of Research Findings: Csfs For Bim Implementation In Hong Kongmentioning
confidence: 99%
“…Moreover, some skilled and experienced teams including design teams can better the operation of the company, so the top management is willing to spend money to support the BIM development in the company further. Interviewee C considered item 5 – client’s acceptance with BIM projects (Harding et al , 2014; Kassem et al , 2012) as also vital. For item 5, different clients have their concerns and needs.…”
Section: Discussion Of Research Findings: Csfs For Bim Implementation In Hong Kongmentioning
confidence: 99%
“…Also, Lu et al (2017) and Olawumi et al (2017) highlighted some BIM functionalities in enhancing building sustainability, such as design analysis to evaluate energy performance and carbon emission analyses, daylighting analysis and sustainable material selection. Akinade et al (2015) and Olawumi and Chan (2018d) also discussed some benefits of integrating smart and sustainable practices in construction projects to include (1) enhancing the productivity and efficiency of construction projects (Gu and London, 2010), (2) real-time sustainable design analysis and simulation (Kivits and Furneaux, 2013), (3) minimize carbon emission and footprints (Hope and Alwan, 2012) and (4) improving building energy efficiency (Boktor et al , 2014; Harding et al , 2014), among others. However, despite all these benefits derivable from implementing smart sustainable practices in construction projects; Marsal-Llacuna et al (2015) revealed that project stakeholders tend toward the sole adoption of BIM more than implementing the two innovations.…”
Section: Smart and Sustainable Practices: Salient Issues In The Built Environmentmentioning
confidence: 99%
“…Nustatyta, kad BIM technologijų taikymo projekto dalyvių bendradarbiavimo galimybės yra plačios ir BIM dažnai naudojamas siekiant atlikti vidaus apšvietos ir inžinerinių sistemų analizes. Mokslininkų išnagrinėtas sėkmingas taikymas parodo, kaip BIM padeda įgyvendinti tvarios ir žaliosios statybos reikalavimus (Harding et al, 2014). BIM vis plačiau diegiamas ir naudojamas visame pasaulyje ne tik statybos, bet ir pastato eksploatavimo metu, t. y. būtina pabrėžti, kad BIM metodologijos taikymas visą statinių gyvavimo laikotarpį suteikia naudų, išreikštų kokybės, ekonominių rodiklių, laiko ir kitais projekto parametrais (Pavlovskis et al, 2017).…”
Section: Literatūros Analizėunclassified